CUIDADOS DE ENFERMAGEM ONCOLÓGICA HUMANIZADOS - Paulo Alexandre Oliveira Marques; Ana Sofia Magalhães Lopes; Ana Lúcia Barbosa Ribeiro; Daniela Francisca de Oliveira Santos (Universidade Federal do Paraná, 2024)
Editorial.